Desenhos organizacionais e atuaç\~ao de think tanks governamentais: Uma análise comparativa internacional - Salvador Teixeira Werneck Vianna; Danilo Santa Cruz Coelho; Alexandre dos Santos Cunha (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The objective of this article is to describe and analyze some of the main characteristics related to the functioning and organizational structures of two governmental research institutions, the CPB Netherlands Bureau for Economic Policy Analysis (CPB) and the Korea Development Institute (KDI), which are international references. The choice of these institutions was due to the fact that their size and attributions are very similar to those of the main Brazilian governmental organization of research in public policies, the Ipea. The main idea is, from the lessons extracted about the forms of action and institutional characteristics of those organizations, to draw attention to the debate about possible alternatives of innovations and trajectories which could be potentially incorporated by Ipea.
Keywords: I23; 330; think tanks; governmental organizations of research in public policies; KDI; CPB; Ipea